Understanding the effects of government spending on consumption - Jordi Galí; David López-Salido; Javier Vallés (European Central Bank (ECB), 2004)
Recent evidence on the effect of government spending shocks on consumption cannot be easily reconciled with existing optimizing business cycle models. We extend the standard New Keynesian model to allow for the presence of rule-of-thumb (non-Ricardian) consumers. We show how the interaction of the latter with sticky prices and deficit financing can account for the existing evidence on the effects of government spending.
Keywords: E32; E62; 330; fiscal multiplier; government spending; rule-of-thumb consumers; Taylor rules